PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 036 SINTONG KECAMATAN TANAH PUTIH - Norliza Norliza; Zulkifli Zulkifli; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of this research is IPA learning outcomes students is low, because teachers still use the lecture method in teaching and learning so that students are passive in the following study. This research aims to improve IPA learning outcomes students fifth grade SD Negeri 036 Sintong which number of students are 20 people. This research is a classroom action research conducted in two cycles. Each cycle consists of 3 (three) meetings consisting of two (2) times the material and 1 (one) Replay times daily. Data collection instruments in this study is observation sheet teacher activities, student activities observation sheet and test results of learning. The activities of teachers in the first cycle is 45% the first meeting and the second meeting increased to 65%. At the first meeting of the second cycle of 80% and increased to 90%. Furthermore, the results of data analysis of student activity in the first cycle the first meeting and the second meeting 45% increase to 60%. In the second cycle the first meeting and the second meeting of the 75% increase to 85%. From the results of this study showed that student learning has increased the average student learning outcomes in basic score is 59.7 increased in the first cycle to 68.25 and increased again in the second cycle is 76.5. For mastery learning on the base score is a 40% increase in the first cycle to 65% increase again in the second cycle to 90%. Thus we can conclude that if applied problem-based learning model can improve IPA learning outcomes fifth grade students of SD Negeri 036 Sintong.Keywords: Problem Based Learning Model, IPA Learning Outcomes